2017
DOI: 10.18051/univmed.2017.v36.34-41
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera extract reduces 8-oxo-2'-deoxyguanosine levels and improves total antioxidants in streptozotocin-induced diabetic rats

Abstract: BACKGROUNDDiabetes mellitus is a chronic disease caused by lack of insulin production in the pancreas or by insulin resistance, the disease being characterized by elevated blood glucose levels. Hyperglycemia in diabetes could lead to oxidative stress due to the rise in 8-oxo-2'-deoxyguanosine (8-oxo-dG) levels and the decrease in levels of total antioxidant status (TAS). The purpose of this study was to assess the effect Aloe vera extract on 8-oxodG level and total antioxidant status in diabetic rat testis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…DNA fragmentation and the intracellular concentration of 8-oxo-2′-deoxyguanosine were also increased significantly in diabetic patients (Shin et al 2001 ; Rama Raju et al 2012 ). Aloe vera extract significantly reduces the level of 8-oxo-dG and DNA fragmentation in STZ-induced diabetes (Christijanti et al 2017 ; Christijanti et al 2019b ). Haritha et al ( 2014 ) reported that oxidative stress was lowered by the oral administration of A. vera gel extract at a dose of 300 mg/kg body weight.…”
Section: Aloe Vera and Stz-induced Diabetesmentioning
confidence: 99%
“…DNA fragmentation and the intracellular concentration of 8-oxo-2′-deoxyguanosine were also increased significantly in diabetic patients (Shin et al 2001 ; Rama Raju et al 2012 ). Aloe vera extract significantly reduces the level of 8-oxo-dG and DNA fragmentation in STZ-induced diabetes (Christijanti et al 2017 ; Christijanti et al 2019b ). Haritha et al ( 2014 ) reported that oxidative stress was lowered by the oral administration of A. vera gel extract at a dose of 300 mg/kg body weight.…”
Section: Aloe Vera and Stz-induced Diabetesmentioning
confidence: 99%
“…These results are in agreement with (Sadri et al ., 2017)who observed that, Plasma levels of MDA were significantly increased While antioxidant enzymes such as SOD and PON1 activities were significantly decreased in diabetic rats received an intraperitoneal injection of STZ(55 mg/kg; i.p)in comparison with normal control rats. In addition, Christijanti et al . (2017) reported that the 8-oxo-dG levels were significantly increased in diabetic rats received an intraperitoneal injection of STZ (65 mg/kg; i.p) .…”
Section: Discussionmentioning
confidence: 99%
“…18 Other researchers state that peel extracts can significantly reduce serum 8-oxo-dG levels compared to the gel. 19…”
Section: Introductionmentioning
confidence: 99%